Enhancing Students’ Life Skills through Cross-Cultural Education and Collaboration between Indonesia and Thailand - Rohana Rohana; Sri Wahyu Indrawati; Indah Anggraini Yusanti; Ninin Non Ayu Salmah; Diana Widhi Rachmawati; Etty Pratiwi; Riyanto Riyanto; Padilah Padilah (Jurnal Abdimas Cendekiawan Indonesia, 2025)
The Sharing non-governmental organization actively facilitates collaboration among Indonesian academics through International Community Service (PKM) initiatives as a realization of the Tridharma Perguruan Tinggi. This program, which has been implemented four times, recently engaged hundreds of participants from various Indonesian universities in partnership with the Embassy of the Republic of Indonesia in Kuala Lumpur, PPI UPSI Malaysia, and higher education institutions in Indonesia and Malaysia. Guided by national education regulations, including Law No. 20 of 2003 on the National Education System and Law No. 12 of 2012 on Higher Education, this PKM program aims to apply academic knowledge, foster entrepreneurship, and address social challenges, particularly in empowering Indonesian Migrant Workers (PMI). The activities employed hybrid approaches combining online and offline workshops, training, and interactive discussions focused on improving participants’ life skills in health, entrepreneurship, financial management, foreign language proficiency, and cross-cultural understanding. The program was held at Lukmanulhakeem School in Yala, Thailand, involving lecturers and students from Universitas PGRI Palembang and partner universities. The results revealed multidimensional benefits: (1) developing leadership and collaboration skills among students and lecturers; (2) strengthening institutional networks and accreditation for universities; and (3) providing tangible contributions to society and government through the empowerment of migrant workers. Moving forward, this initiative is expected to continue each semester in various countries with enhanced content, strategic partnerships, and innovative methods to broaden its social and educational impact.